Fatores determinantes na escolha do Brasil como exportador de serviços de tecnologia da informação - Cardoso, Flavio Cesar Moreira (2006)
The export of information technology software services, also known as ¿offshore outsourcing¿, has raised debates in the media as well as in the academy. A lot has been written about the success of India, Ireland and Israel, the ¿3Is¿, but empirical data about Brazil is still hard to find. This dissertation proposes to identify success factors for Brazil to be chosen as a preferred location for offshore outsourcing based on a case study of an American multinational corporation, with branches in Brazil, that is systematically choosing Brazil as a preferred location for its offshore outsourcing operations. Concepts of economic globalization, internationalization of services and success factors for offshore outsourcing will be presented in the literature review and based on available literature focused on Brazil, a model of eight success factors is proposed. The empirical research was grounded on multiple data sources but the analysis was focused on a database of 219 deals that were conducted from September 2005 to May 2006, out of which Brazil was selected 57 times. The results confirm the proposed model of eight success factors. The final conclusions suggest that the process of identifying a country to perform the offshore activities is complex and that not all factors will be present at the same time, and more than that, in some cases intangible factors, such as relationship networks and emotional links with the country, have a higher weight in the decision. The results can be used in the future for in depth researches that differentiate Brazil from other countries in the offshore outsourcing market.